An Efficacious Transgenic Strategy for Triple Knockout of Xeno-Reactive Antigen Genes GGTA1, CMAH, and B4GALNT2 from Jeju Native Pigs - Seungwon Yoon; Seulgi Lee; Chungyu Park; Hyunyong Choi; Minwoo Yoo; Sang Chul Lee; Cheol-Ho Hyun; Nameun Kim; Taeyoung Kang; Eugene Son; Mrinmoy Ghosh; Young-Ok Son; et al. (Vaccines, 2022)
Pigs are promising donors of biological materials for xenotransplantation; however, cell surface carbohydrate antigens, including galactose-alpha-1,3-galactose (α-Gal), N-glycolylneuraminic acid (Neu5Gc), and Sd blood group antigens, play a significant role in porcine xenograft rejection. Inactivating swine endogenous genes, including GGTA1, CMAH, and B4GALNT2, decreases the binding ratio of human IgG/IgM in peripheral blood mononuclear cells and erythrocytes and impedes the effectiveness of α-Gal, Neu5Gc, and Sd, thereby successfully preventing hyperacute rejection. Therefore, in this study, an effective transgenic system was developed to target GGTA1, CMAH, and B4GALNT2 using CRISPR-CAS9 and develop triple-knockout pigs. The findings revealed that all three antigens (α-Gal, Neu5Gc, and Sd) were not expressed in the heart, lungs, or liver of the triple-knockout Jeju Native Pigs (JNPs), and poor expression of α-Gal and Neu5G was confirmed in the kidneys. Compared with the kidney, heart, and lung tissues from wild-type JNPs, those from GGTA1/CMAH/ B4GALNT2 knockout-recipient JNPs exhibited reduced human IgM and IgG binding and expression of each immunological rejection component. Hence, reducing the expression of swine xenogeneic antigens identifiable by human immunoglobulins can lessen the immunological rejection against xenotransplantation. The findings support the possibility of employing knockout JNP organs for xenogeneic transplantation to minimize or completely eradicate rejection using multiple gene-editing methods.